Non‐uniform mesh for embroidered microstrip antennas. Issue 8 (19th May 2017) - Zhang, Shiyu; Whittow, William; Seager, Rob; Chauraya, Alford; Vardaxoglou, J(Yiannis) C.
Abstract : This study presents a non‐uniform meshed embroidered structure for wearable microstrip patch antennas. The non‐uniform meshed patch antenna (NMPA) has significantly less conductor coverage than a conventional patch antenna without significantly compromise the antenna performance. For wearable applications, less conductor coverage reduces the usage of the specialised conductive materials which are currently expensive. The embroidered NMPA reduced manufacturing cost and improves the flexibility. In this study, the surface current distribution and the effect of the meshing size of NMPAs have been simulated and analysed. Fully textile embroidered NMPA on felt substrate has been fabricated and measured. Representative results showed the NMPA had a 60% total antenna efficiency with 20% conductor area coverage.